Effectiveness of E-Rapor Implementation: Literature Review - Maula, Faradina Milla; Raharja, Setya; Wibowo, Udik Budi (Universitas Pendidikan Ganesha, 2024)
Implementing E-Rapor (Electronic Report) in education has become an exciting research topic that has captured the attention of numerous researchers. Based on the findings of a literature review, E-Rapor aims to bring benefits and positive impacts to the field of education, promoting its growth in the current digital era. However, researchers have also noted several limitations in using the E-Rapor-based information system, including difficulties in its application for information processing, competence planning, and data management. This research seeks to analyze gaps in the learning outcomes achieved by students when the E-Report application system is implemented compared to traditional or manual assessment methods. The data collection method employed in this study is a literature review, which involves gathering secondary data from various reputable sources. As for the research instrument used, the researchers have formulated five research questions that serve as valuable guides throughout the data collection process. The results of the discussion show that E-Reports are useful for regularly assessing student abilities by educators and school employees, allowing quick intervention when necessary, and increasing overall educational efficiency. Due to this, the author recommends further research to understand the impact of using E-Reports on learning outcomes and educational management to be comprehensive.